PENGARUH GAME ONLINE TERHADAP AKTIVITAS BELAJAR PESERTA DIDIK DI SD - Arif Budhiman; Heru Purnomo (Universitas Muhammadiyah Purwokerto, 2022)
The influence of online games among elementary school children regarding the positive and negative impacts of online games on the learning activities of students in elementary school. This article is the result of an analysis of the literature on the topic being discussed. From the results of the analysis and literature review, it shows that the influence of online games among elementary school children has a positive and negative impact. The purpose of the study was to determine the effect of online games on the learning activities of students in elementary school. This type of research is a research with a literature review method. The data analysis technique is by collecting, reading, summarizing the results and recording important information contained in various journals related to the research being conducted. The results show that online games have a positive and negative impact on the learning activities of students in elementary school. The conclusion in this study is that online games will not have a bad impact if used according to their portions, but will have a bad impact and affect the learning activities of students in elementary school if used excessively.